Сказки из волшебной лампы - Пыльцын Михаил (Серия "Сказки БЭСТ", 2013)
Экземпляры: ф.23 (20250220) / Инвентарный номер: 65616 / Цена: / Сис.шифр: 82.3(3)-4 / Авт.знак: С 42 / ГРНТИ: 17.82.93 / ББК: 82.3(3)-45